HUBUNGAN RELIGIOSITAS DENGAN MULTIKULTURALISME PADA GURU AGAMA SEKOLAH NEGERI DI JAKARTA - Dionisius Egho; Hana Panggabean (Universitas Katolik Indonesia Atma Jaya, 2020)
Intolerance and radicalism that occur in the community proved to have entered the realm of the world of education, especially in schools and colleges. The role of educators in instilling values in students is important. So the rise of religious intolerance and radicalism in the world of education raises questions about the role of educators, especially religious teachers. This research tries to explain how the relationship between religiosity and multiculturalism in religion teachers in public schools. Research participants are religion teachers in state schools in Jakarta (N = 152, 83 boys and 69 girls).The sampling technique used was accidental, in the data retrieval stage.The level of religiosity of religious teachers was measured by the adaptation measuring instrument The Centrality Scale (CRS) which had a reliability value of 0.83 (Huber and Huber, 2012). While the multiculturalism attitude of religious teachers was measured by the adaptation measuring instrument Multicultural Efficacy Scale which has a reliability value of 0.87 (Guyton & Wesche, 2005). Research results show that religiosity has a significant and positive relationship with multiculturalism. This is seen from the correlation value of 0.319, which confirms that a high level of religiosity will result in a high attitude of multiculturalism, and vice versa.